Apicomplexans: a conoid ring unites them all - Guizetti, Julien; Frischknecht, Friedrich (PLoS biology, 2021)
Apicomplexan parasites are defined by complex apical structures, which are necessary for interaction with incredibly diverse host cells. Two studies now amend a long-standing paradigm by showing conservation of an essential ring structure in the entire phylum.
Gesehen am 06.08.2021